Adobe InDesign CS6 revealed c Chris Botello - Botello, Chris (Delmar Cengage Learning, 2013)
Chapter 1: Getting to know InDesign -- Chapter 2: Working with text -- Chapter 3: Setting up a document -- Chapter 4: Working with frames -- Chapter 5: Working with color -- Chapter 6: Working with placed images -- Chapter 7: Creating graphics -- Chapter 8: Exploring effects and advanced techniques -- Chapter 9: Working with tabs and tables -- Chapter 10: Making books, tables of contents, and indexes --Chapter 11: Preparing, packaging, and exporting documents for print